Challenging biliary strictures: pathophysiological features, differential diagnosis, diagnostic algorithms, and new clinically relevant biomarkers - part 1. (June 2020) - Dumonceau, Jean-Marc; Delhaye, Myriam; Charette, Nicolas; Farina, Annarita
It is frequently challenging to make the correct diagnosis in patients with biliary strictures. This is particularly important as errors may have disastrous consequences. Benign-appearing strictures treated with stents may later be revealed to be malignant and unnecessary surgery for benign strictures carries a high morbidity rate. In the first part of the review, the essential information that clinicians need to know about diseases responsible for biliary strictures is presented, with a focus on the most recent data. Then, the characteristics and pitfalls of the methods used to make the diagnosis are summarized. These include serum biomarkers, imaging studies, and endoscopic modalities. As tissue diagnosis is the only 100% specific tool, it is described in detail, including techniques for tissue acquisition and their yields, how to prepare samples, and what to expect from the pathologist. Tricks to increase diagnostic yields are described. Clues are then presented for the differential diagnosis between primary and secondary sclerosing cholangitis, IgG4-related sclerosing cholangitis, cholangiocarcinoma, pancreatic cancer, autoimmune pancreatitis, and less frequent diseases. Finally, algorithms that will help to achieve the correct diagnosis are proposed.